1995
DOI: 10.1074/jbc.270.1.313
|View full text |Cite
|
Sign up to set email alerts
|

Binding Characteristics of Ciliary Neurotrophic Factor to Sympathetic Neurons and Neuronal Cell Lines

Abstract: Ciliary neurotrophic factor (CNTF) is a cytokine whose actions are largely restricted to the nervous system because of the predominant neuronal distribution of its receptor, CNTFR alpha. In this study, we sought to define the binding characteristics of CNTF to cultured sympathetic neurons and cell lines of neuronal origin. We report that 125I-CNTF binds to cultured sympathetic neurons, MAH, PC12, and EW-1 cells via high and low affinity receptors that can be distinguished on the basis of their dissociation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
4
17
0
Order By: Relevance
“…Thus, reduced Cntf levels could contribute to this phenotype. Levels of Cntf protein in human peripheral nerves are much lower than in mice (M.S., unpublished observations), and human CNTF is less active than the mouse Cntf protein, even in human target cells (41). Thus, reduced gene expression might be more critical in humans in comparison to mice.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, reduced Cntf levels could contribute to this phenotype. Levels of Cntf protein in human peripheral nerves are much lower than in mice (M.S., unpublished observations), and human CNTF is less active than the mouse Cntf protein, even in human target cells (41). Thus, reduced gene expression might be more critical in humans in comparison to mice.…”
Section: Discussionmentioning
confidence: 97%
“…This subunit is present in intact neurons in the SCG (Wong et al, 1995), DRG (Gardiner et al, 2002), and cranial and spinal motor nuclei (Watanabe et al, 1996). gp130 mRNA does not change after axotomy in SCG (Banner and Patterson, 1994), DRG (Gardiner et al, 2002; Brazda et al, 2009) or facial motor neurons (Haas et al, 1999).…”
Section: Cytokine Receptors In Normal and Axotomized Peripheral Neuronsmentioning
confidence: 99%
“…1996). Another group found that LIF and CNTF treatment of neurons can inhibit subsequent binding of CNTF, providing evidence of reduced receptor surface expression, but they did not examine total receptor levels (Wong et al. 1995).…”
Section: Discussionmentioning
confidence: 99%